2005년 암의 경제적 비용부담 추계 - 김진희; 함명일; 박은철; 박재현; 박종혁; 김성은; 김성경; Kim, Jin-Hee; Hahm, Myung-Il; Park, Eun-Cheol; Park, Jae-Hyun; Park, Jong-Hyock; et al. (Journal of preventive medicine and public health, 2009)
Objectives : The objective of this study is to estimate the economic costs of cancer on society. Methods : We estimated the economic burden of people with cancer in South Korea. To perform the analysis, we reviewed the records of people who were cancer patients and those who were newly diagnosed with cancer. The data was compiled from the National Health Insurance Corporation, which included the insurance claims database, a list of cancer patients, a database that records the cancer rates, the Korea Central Cancer Registry Center s cancer patient registry database and the Korea National Statistical Office s causes of death database. We classified the costs as related to cancer into direct costs and indirect costs, and we estimated each cost. Direct costs included both medical and non-medical care expenses and the indirect costs consisted of morbidity, mortality and the caregiver's time costs. Results : The total economic costs of cancer in South Korea stood at 14.1 trillion won in 2005. The largest amount of the cost 7.4 trillion won, was the mortality costs. Following this were the morbidity costs (3.2 trillion won), the medical care costs (2.2 trillion won), the non-medical care costs (1.1 trillion won) and the costs related to the caregiver's time (100 billion won). As a result, the economic cost of cancer to South Korea is estimated to be between 11.6 trillion won to 14.1 trillion won for the year 2005. Conclusions : We need to reduce the cancer burden through encouraging people to undergo early screening for cancer and curing it in the early stage of cancer, as well as implementing policies to actively prevent cancer.